HARMONIZING SOUND AND SCRIPT: INTEGRATING PHONETIC SYMBOLS WITHIN THE LEXICAL APPROACH TO IMPROVE EFL LISTENING SKILL - Susanto, Susanto; Nanda, Deri Sis (University of Kuningan, 2024)
Phonetic symbols play a crucial role in linguistics by providing a systematic means to represent the phonological attributes of words, encompassing both pronunciation and orthographic manifestations. Their primary function is to enhance the identification and comprehension of words in spoken and written language contexts. In the realm of English as a Foreign Language (EFL), this study explores the utilization of phonetic symbols to enhance students’ clarity and understanding when engaging with the English lexicon. This application is integrated into the framework of the lexical approach, a pedagogical paradigm that underscores the significance of mastering vocabulary and language components such as collocations, phrases, and idiomatic expressions. The participants were 46 students enrolled in phonetics and phonology courses at the English Language Education Department, Bandar Lampung University, Indonesia. The research design follows a classroom action research model, aiming to enhance students’ listening skills through the strategic incorporation of phonetic symbols within the lexical approach framework. Based on observations and assessments, the study reveals that proficiency in recognizing and differentiating phonetic symbols contributes to students’ comprehension of words embedded in spoken texts. Furthermore, the results from the testing phase indicate that 36 out of 46 students achieved a passing score of 75 or higher, reflecting a success rate of 78%. This achievement aligns with the predetermined research success criteria, highlighting the positive impact of incorporating phonetic symbols within the lexical approach for improving students’ language skills. The implications suggest that incorporating phonetic symbols within the lexical approach framework can serve as a valuable pedagogical strategy for educators aiming to enhance students listening skills and overall language proficiency in an EFL context.